High blood pressure - Fahey, Tom, 1961- (At your fingertips (London, England), 2004)
High Blood Pressure - the 'at your fingertips' guide is the essential handbook for straightforward and medically accurate information about your blood pressure. Packed full of information about how to get your blood pressure down - and keep it down, it is a must for anyone interested in controlling their blood pressure.